Generation of iPSC line from a Joubert syndrome patient with compound heterozygous mutations in CPLANE1 gene - Mazzotta C.; Serpieri V.; Orsi A.; Cavan S.; Rossi E.; Stanzial F.; Valente E.M. (Stem Cell Research, 2024)
We generated iPSC line using skin fibroblasts obtained from a female patient affected by Joubert syndrome, caused by two compound heterozygous variants (c.143G > A; p.Gly48Glu and c.1784 T > G; p.Leu595Ter) in CPLANE1. We used Sendai-virus-based technique for reprogramming and then we applied karyotype analysis, to exclude possible acquired big rearrangements. We verified the presence of the same STR profile as fibroblasts, the stem cell state (by immunofluorescence and qPCR) and, finally, the pluripotency state (by in vitro trilineage differentiation).